Assessment of the Threats and Weaknesses of Entrepreneurship Education in the Management Universities in South-East, Nigeria - Obiweluozor, Nkechi; Ogunbiyi, Oluwadare Deji (NIU Journal of Social Sciences; Vol 9 No 1 (2023): NIU Journal of Social Sciences, Vol. 9 No. 1, March 2023, 2023)
The study assessed the treats and weaknesses of entrepreneurship education in the management of Southeast Universities, Nigeria. The study was guided by two objectives, two research questions and hypotheses. A descriptive survey research design was adopted for the study. The sample for the study was composed through a multi-stage sampling technique. This gave a sample of 463 respondents used for the study. A questionnaire titled Treats and Weaknesses of Entrepreneurship Education Questionnaire (TWEEQ) was designed and used for the study. This instrument was validated and the overall reliability ascertained to be 0.77. From data collected, mean and standard deviation were used to answer the research questions while T-test statistic was used to test the null hypotheses at 0.05 level of significance. Results show that universities have opportunities of managing entrepreneurship education. Results further show that there is no significant difference between the mean responses of lecturers and coordinators on the management of entrepreneurship education in the management of Universities in South East, Nigeria. Based on this, the work recommends that, the universities authorities should make provision for lecturers to go for workshops or seminars so as to be exposed to current trends in EED programme. The Federal Government of Nigeria should maintain a policy aimed at making adequate fund available for entrepreneurship education in the universities. Keywords: Threats, Weaknesses, Entrepreneurship, Education and University.